Allometric and Stoichiometric Traits Predict Nutrient Excretion Rates by Benthic Consumers - Villnäs, Anna; Mäkelin, Saara; Vanni, Michael J. (Frontiers in Marine Science, 2022)
Benthic consumers profoundly impact nutrient regeneration in coastal marine ecosystems. The concurrent nutrient imbalance and warming of our coastal seas will change the nutritional requirements and metabolic demands of these consumers, which may affect their ability to recycle nitrogen and phosphorous. Here we explore whether nutrient excretion rates of two benthic consumers, the Baltic clam (Macoma balthica) and the invasive spionid polychaete (Marenzelleria spp.) can be quantified with basic biological traits across seasons using allometric and stoichiometric relationships. We found species-specific N and P excretion rates that positively link to allometric traits, i.e., per individual rates increased with body mass and temperature; thus, high mass-specific excretion rates characterized small relative to large macrofaunal individuals. Interestingly, our body size scaling coefficients diverge from predictions by the metabolic theory of ecology (MTE) and the universal model of excretion. Stoichiometric traits and stable isotope signatures (δ 13C and δ 15N) explained a minor additional proportion of variability in excretion rates among species. The excretion rates also varied strongly seasonally, with the highest nutrient recycling rates during summer months, when community NH4-N and PO4-P excretion clearly exceeded net sediment efflux. The seasonal pattern emphasized that changes in temperature and food availability drove metabolic processes and thus excretion rates of the benthic consumers, and indicated that these effects could outweigh the importance of animal biomass. Our results highlight the benefits of using allometric and stoichiometric traits when quantifying species-specific contributions to nutrient recycling in coastal marine environments, and in predicting alteration of function in response to environmental change.